Interleukin-1β Triggers p53-Mediated Downmodulation of CCR5 and HIV-1 Entry in Macrophages through MicroRNAs 103 and 107 - Robert Lodge (American Society for Microbiology, 2020)
ABSTRACT Macrophages are a target of human immunodeficiency virus type 1 (HIV-1) and may serve as a viral reservoir during antiretroviral therapy (ART). Their susceptibility to HIV-1 infection is subject to variations from permissiveness to resistance depending on their origin, tissue localization, and polarization profile. This is in part due to the expression of regulatory microRNAs. Here, we identify two microRNA paralogs, microRNA 103 (miR-103) and miR-107, as regulators of CCR5 expression that are upregulated in noninfected bystander cells of HIV-1-infected-monocyte-derived macrophage (MDM) cultures. Transfection of microRNA 103 mimics in MDMs reduced CCR5 expression levels and inhibited CCR5-dependent HIV-1 entry, whereas the corresponding antagomirs enhanced virus spread in HIV-infected MDMs. Treatment of MDMs with interleukin-1β (IL-1β) enhanced microRNA 103 expression, a condition that we found contributed to the reduction of CCR5 mRNA in IL-1β-exposed MDMs. Interestingly, we show that the induction of miR-103/107 expression is part of a tumor suppressor p53 response triggered by secreted IL-1β that renders macrophages refractory to HIV-1 entry. In a more physiological context, the levels of microRNAs 103 and 107 were found enriched in tissue-resident colon macrophages of healthy donors and alveolar macrophages of individuals under antiretroviral therapy, conceivably contributing to their relative resistance to HIV-1 infection. Overall, these findings highlight the role of p53 in enforcing proinflammatory antiviral responses in macrophages, at least in part, through miR-103/107-mediated downmodulation of CCR5 expression and HIV-1 entry. IMPORTANCE Macrophages are heterogeneous immune cells that display varying susceptibilities to HIV-1 infection, in part due to the expression of small noncoding microRNAs involved in the posttranscriptional regulation of gene expression and silencing. Here, we identify microRNAs 103 and 107 as important p53-regulated effectors of the antiviral response triggered by the proinflammatory cytokine IL-1β in macrophages. These microRNAs, which are enriched in colon macrophages of healthy donors and alveolar macrophages of HIV-infected individuals under antiretroviral therapy, act as inhibitors of HIV-1 entry through their capacity to downregulate the CCR5 coreceptor. These results highlight the important role played by miR-103/107 in modulating CCR5 expression and HIV-1 entry in macrophages. They further underscore a distinct function of the tumor suppressor p53 in enforcing proinflammatory antiviral responses in macrophages, thus providing insight into a cellular pathway that could be targeted to limit the establishment of viral reservoirs in these cells.